2023
DOI: 10.3390/jcm12020539
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pulp Tissue Viability and Cytotoxicity of Pulp Capping Agents

Abstract: The present research study assessed the cell viability and cytotoxic effect of mineral tri-oxide aggregate (MTA), Tetric N-Bond Universal bonding agent, Theracal PT (pulpotomy treatment), and platelet-rich fibrin (PRF) as pulp capping agents on human dental pulp stem cells (hDPSCs). The cells were isolated from the pulp tissue of an extracted healthy permanent third molar. After four passages in Dulbecco’s Modified Eagle’s Medium, the primary cells were employed for the investigation. The test materials and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…7. The results of this study are consistent with those of previous research, indicating that TPT does not exhibit cytotoxicity and supports cell proliferation [61]. Additionally, the results aligned with previous cell toxicity experiments based on the dilution ratios of TPT and TLC [15].…”
Section: Discussionsupporting
confidence: 92%
“…7. The results of this study are consistent with those of previous research, indicating that TPT does not exhibit cytotoxicity and supports cell proliferation [61]. Additionally, the results aligned with previous cell toxicity experiments based on the dilution ratios of TPT and TLC [15].…”
Section: Discussionsupporting
confidence: 92%
“…Since the material is intended for human skin cleansing applications, cytotoxicity testing is required to guarantee its safety. 30 To calculate sample SiO 2 /lignin#2 for cytotoxicity assessment, the absorbance readings of HaCaT cells, L929 cells, and RAW264.7 cells exposed to samples of different concentrations at 25, 50, 100, 200, and 400% were compared with that of 0% concentration. 31 To obtain the relative percentage of cell viability, as shown in Figures S3−S4, the values of 25, 50, 100, 200, and 400% concentrations remained similar to 0% concentrations for the three cell types, indicating that the cytotoxicity levels of the sample SiO 2 /lignin#2 were relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…Since the material is intended for human skin cleansing applications, cytotoxicity testing is required to guarantee its safety . To calculate sample SiO 2 /lignin#2 for cytotoxicity assessment, the absorbance readings of HaCaT cells, L929 cells, and RAW264.7 cells exposed to samples of different concentrations at 25, 50, 100, 200, and 400% were compared with that of 0% concentration .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, several studies showed that treatment of the open apex with calcium silicate materials could improve the efficiency of this treatment within one visit [ 7 , 8 , 9 ]. These materials showed their efficiency in different endodontic treatments such as apicoectomy [ 10 ], perforation [ 11 ], pulpotomy [ 12 ], open apex [ 5 ], pulp cupping [ 13 ], and resorption [ 14 ]. These calcium-silicate-based materials, called bioceramics, have excellent physicochemical, mechanical, and biological properties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%